'They say we are all zombies': Rethinking the role of audiences in a mediatized international conflict. (April 2023) - Vihalemm, Triin; Juzefovičs, Jānis
This article contributes to the conceptualization of international conflict mediatization through the lenses of 'audience logic' instead of the usual 'media logic' perspective. The former is defined here as beliefs about the workings of the media system that are held by audiences and constructions of their own identities as media users. The empirical analysis is about strategies used by Baltic Russian-speakers in making sense of media and news during the Russia-Ukraine conflict during 2013–2019. The authors propose elaborating the conceptualization of the audience and further inquiry into the resources for audience empowerment to alter today's asymmetrical publics/elites power dynamics.